2017
DOI: 10.1093/mnras/stx1659
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlating Planck tSZ with RCSLenS weak lensing: implications for cosmology and AGN feedback

Abstract: We present measurements of the spatial mapping between (hot) baryons and the total matter in the Universe, via the cross-correlation between the thermal Sunyaev-Zeldovich (tSZ) map from Planck and the weak gravitational lensing maps from the Red Sequence Cluster Survey (RCSLenS). The cross-correlations are performed on the map level where all the sources (including diffuse intergalactic gas) contribute to the signal. We consider two configuration-space correlation function estimators, ξ y−κ and ξ y−γ t , and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 45 publications
4
100
0
Order By: Relevance
“…Since at most 15% of the measured signal comes from unbound gas if we restrict the overall IGM contribution to be that fraction of the overall signal then only models with α ≤ 1.5 are compatible with the data. In other words, the mean temperature of the IGM free electron gas would beT e ≤ 7 × 10 6 K. The data from Hojjati et al (2016) shown in Fig 4a are even more restrictive. These authors compared their measurements against the predictions of the halo model and from numerical simulations that included diffuse gas.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Since at most 15% of the measured signal comes from unbound gas if we restrict the overall IGM contribution to be that fraction of the overall signal then only models with α ≤ 1.5 are compatible with the data. In other words, the mean temperature of the IGM free electron gas would beT e ≤ 7 × 10 6 K. The data from Hojjati et al (2016) shown in Fig 4a are even more restrictive. These authors compared their measurements against the predictions of the halo model and from numerical simulations that included diffuse gas.…”
Section: Resultsmentioning
confidence: 93%
“…What is more relevant is that the overall shape is very different. Hojjati et al (2016) found that the shape of the correlation function and power spectrum was strongly dependent on physical processes undergone by baryons in halos such as radiative cooling, star formation, supernovae winds and AGN feedback. For instance, AGNs expel gas to large distances from the center of halos, lowering the signal at small scales.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations